2010
DOI: 10.1007/s00417-010-1471-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of ocular response analyzer measurements and their correlation with central corneal thickness

Abstract: The interobserver reproducibility of ORA measurements was almost perfect for IOPcc, CRF, and CH. The intraobserver short-term reproducibility was almost perfect for IOPcc and substantial for CRF and CH, for all observers. The significant correlation between CCT and CRF, and no association between IOPcc and CCT, are in agreement with previous studies. There was no significant correlation between CH and CCT in our study. This device might be useful in glaucoma diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
4
19
1
2
Order By: Relevance
“…When a simple regression line was applied, a positive relationship was revealed (i.e., the higher the CCT, the higher the CH and CRF and vice versa). The results of several studies [18,21] agree with our results, while other studies demonstrated that only CRF and not CH showed a strong correlation with CCT [22,23]. However, in our study, the correlation coefficients (Table 3) imply that CH, CRF, and CCT are related, but are not measurements of the same biomechanical parameter.…”
Section: Discussionsupporting
confidence: 53%
“…When a simple regression line was applied, a positive relationship was revealed (i.e., the higher the CCT, the higher the CH and CRF and vice versa). The results of several studies [18,21] agree with our results, while other studies demonstrated that only CRF and not CH showed a strong correlation with CCT [22,23]. However, in our study, the correlation coefficients (Table 3) imply that CH, CRF, and CCT are related, but are not measurements of the same biomechanical parameter.…”
Section: Discussionsupporting
confidence: 53%
“…ORA provides both: IOP and biomechanical properties of the cornea such as corneal hysteresis (CH) and corneal resistance factor (CRF). A corneal-compensated intraocular pressure (IOPcc) has been reported to be less affected by the corneal properties than GAT [1618]. Furthermore, CH and CRF seem to be predictors for the development of glaucoma [19].…”
Section: Introductionmentioning
confidence: 99%
“…The ORA-measurements have shown to be reproducible in several studies [17, 18, 23]. There are only few studies evaluating an influence of repeated ORA measurements or ocular massage on the IOP in healthy subjects [17, 24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters mathematically correlated with CH were developed; these include, the corneal-compensated IOP (IOP), which was empirically developed by comparing prelaser in situ keratomileusis (LASIK) and post-LASIK data, and the corneal resistance factor (CRF), which was designed to maximally correlate with corneal thickness. 6,7,A Other studies [8][9][10] found that Ocular Response Analyzer curves vary according to corneal characteristics. Positive correlations between CH and corneal thickness or IOP were seen.…”
mentioning
confidence: 98%